Critical Evaluation of Afaf Meleis´S Transition Theory: Strengths, Limitations and Applications in Nursing Education; [Evaluación Crítica de la Teoría de Las Transiciones de Afaf Meleis: Fortalezas, Limitaciones y Aplicaciones en la Educación en Enfermería] - Cancino-Jimenez, J (AG Editor (Argentina), 2024)
Introduction: Afaf Meleis’s Transitions Theory addresses how multidimensional transitions impact individuals’ health and well-being, emphasizing the importance of properly managing these transitions. This study aims to critically and reflectively describe this theory by analyzing its strengths, limitations, usefulness, and significance in nursing education. Method: Chinn and Kramer’s theory analysis methodology was used. The description was based on publications from 1994 to 2010, and a critical reflection was performed by searching for evidence in PubMed and CINAHL between 2015 and 2021. The MeSH descriptors “Nursing Theory,” “Models,” and “Nursing” were used, along with the keywords “Transition” and “Transition Theory Meleis,” resulting in a total of 16 selected articles. Results: the Transitions Theory has several strengths and limitations. Among its strengths are its high generalizability and accessibility, allowing for application in various clinical and educational contexts. However, the theory has limited semantic clarity and is complex, which may hinder its full understanding and application. Conclusions: the theory is highly valued in nursing education, providing a valuable theoretical framework for understanding and addressing student transitions. Its application allows for incorporating lived contexts into the educational process, creating equitable and student-centered learning environments. More research is needed in Latin America to evaluate its usefulness and adapt it to regional contexts, promoting meaningful learning both in the classroom and in clinical practice. © 2024; Los autores.